2005
DOI: 10.5194/acpd-5-5127-2005
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aerosol and NO<sub>x</sub> emission factors and submicron particle number size distributions in two road tunnels with different traffic regimes

Abstract: Abstract. Measurements of aerosol particle number size distributions (18–700 nm), mass concentrations (PM2.5 and PM10) and NOx were performed in the Plabutsch tunnel, Austria, and in the Kingsway tunnel, United Kingdom. These two tunnels show different characteristics regarding the roadway gradient, the composition of the vehicle fleet and the traffic frequency. The submicron particle size distributions contained a soot mode in the diameter range D=80–100 nm and a nucleation mode in the range of D=20–40 nm. In… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
27
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 34 publications
(46 reference statements)
6
27
0
1
Order By: Relevance
“…It is obvious that the emission factors of PN 0.05 that includes the major part of total particle number emissions are in good agreement with results reported by others (Imhof et al, 2006 andYli-Tuomi et al, 2005). These authors also estimated emission factors of particle number in various size ranges under real-world conditions.…”
Section: Emission Factors For Hdvs and Ldvssupporting
confidence: 79%
“…It is obvious that the emission factors of PN 0.05 that includes the major part of total particle number emissions are in good agreement with results reported by others (Imhof et al, 2006 andYli-Tuomi et al, 2005). These authors also estimated emission factors of particle number in various size ranges under real-world conditions.…”
Section: Emission Factors For Hdvs and Ldvssupporting
confidence: 79%
“…The geometric standard deviation (GSD) value for the nucleation mode was 1.7 both for the summer and winter. Imhof et al (2005b) measured particle size distributions in two different road tunnels in Graz and Liverpool. They found nucleation mode with GMDs around 15-20 nm in Graz and 25 nm in Liverpool and GSDs of approximately 1.8 and 1.5 respectively.…”
Section: Characteristics Of Road-side Distributionsmentioning
confidence: 99%
“…Imhof et al (2005b) measured the road tunnel soot distributions peaking at around 80-100 nm (GSD∼1.85) in the tunnel in Graz. On the other hand, they reported that the soot mode measured in the traffic tunnel in Liverpool was not clearly distinguishable in the distribution and its GMD was around 45 nm (GSD∼2.22).…”
Section: Characteristics Of Road-side Distributionsmentioning
confidence: 99%
“…18% NO x 11.7 0.027 20-25 m Imhof et al (2005) 7-300 80-100 ca. 18% NO x 13.5 0.048 8-20 m Hueglin et al (2006) 7-1000 100 18% NO x 7.9 20 m Imhof et al (2006) 18-700 80 18% tunnel 1.50 (0.08) 0.21 (0.008) n.a. Abu-Allaban et al (2002) 10-400 <90 14% tunnel 0.52-0.54 n.a.…”
mentioning
confidence: 99%